2022
DOI: 10.3390/ijms232012431
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Influence on Readily Available Inflammatory Markers in OSA—A Pilot Study

Abstract: Obstructive sleep apnea (OSA) is characterized by repetitive upper airway collapse, chronic hypoxia and a proinflammatory phenotype. The purpose of our study was to evaluate readily available inflammatory biomarkers (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cell count (WBC), red cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), mean platelet volume (MPV), WBC-to-MPV ratio (WMR) and lymphocyte-to-C-reactive protein ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…Three studies [46,58,60] reported lower RDW values in OSAS subjects than non-OSAS controls (mean difference range, −0.10 to −0.60), with one reporting a statistically significant difference [60], whereas no between-group difference was reported in another study [57]. In the remaining 16 studies [14,44,45,47-50,52-56,58,61,62], OSAS patients had higher RDW values than non-OSAS subjects (mean difference range, 0.05 to 3.99), with a significant difference in eight [45,47,48,[51][52][53]61]. Since a substantial heterogeneity between studies was observed (I 2 = 91.6%, p < 0.001), random-effects models were used.…”
Section: Results Of Individual Studies and Synthesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies [46,58,60] reported lower RDW values in OSAS subjects than non-OSAS controls (mean difference range, −0.10 to −0.60), with one reporting a statistically significant difference [60], whereas no between-group difference was reported in another study [57]. In the remaining 16 studies [14,44,45,47-50,52-56,58,61,62], OSAS patients had higher RDW values than non-OSAS subjects (mean difference range, 0.05 to 3.99), with a significant difference in eight [45,47,48,[51][52][53]61]. Since a substantial heterogeneity between studies was observed (I 2 = 91.6%, p < 0.001), random-effects models were used.…”
Section: Results Of Individual Studies and Synthesesmentioning
confidence: 99%
“…Of these, 48 were removed because they did not report the studied endpoint (n = 30), did not include the control group (n = 9), investigated pediatric cohorts (n = 4) or different patient groups (n = 2), or were not written in English (n = 3), leaving 17 articles. Since three additional records were identified from Google Scholar and reference lists, a total of 20 manuscripts [14,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] were included in the final analysis (Figure 1). The included studies were published between 2012 [44] and 2022 [60][61][62].…”
Section: Systematic Research and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations